Estudo das diferenças individuais no comportamento de usuárias de tecnologia em serviços de mobilidade urbana - Hino, Marcia Regina Martelozo Cassitas (2018)
With the accelerated process of urbanization, the Brazilian population is currently 85% urban. In countries with an emerging economy, the reduction of urban mobility emerges as one of the main problem with direct impact on the economy and people's quality of life. The mobility difficulties faced in cities are different for men and women. To investigate the phenomenon the study makes use of the theory of individual differences of gender and technology (TRAUTH, QUESENBERRY, MORGAN, 2004), because it is the theoretical lens that most approximates the subjects investigated. The study proposes to investigate how individual differences influence the behavior of technology users in urban mobility services. The research was structured using mixed methods. The data collection was done with qualitative and quantitative methods. In the intermediate phase of analysis, the qualitative data were converted into quantitative and, through the application of statistical methods of regression, to suggest affinity groups. In the interpretation of quantitative and qualitative results, five profiles were defined, demonstrating the influence of individual characteristics on the behavior of technology users in urban mobility services: the safe and technological woman, the discreet and basic woman, the woman in self-discovery, the practical and determined woman, and the free and independent woman. The work enriches the theoretical environment by overcoming the limits in the use of the theory for which it was designed, and contributes with indications of a new proposal of analysis for the phenomenon: the model of individual differences in the behavior of technology use, composed by identity individual identity, context identity and IT identity. The contribution to the literature takes place when the debate on urban mobility and gender is promoted, as well as the knowledge in the area of urban mobility with the perspective of individual characteristics of women. Illuminating the practice, the work contributes to foment the debate on the subject with possible reflections in the improvement of public policies of mobility, and the availability of information to companies that facilitate the access to services of urban mobility and to companies of the chain of transport services urban. In bringing the focus to the subject, the researcher hopes to develop current perspectives that contribute to the accessibility of women to better urban mobility services.